Enhanced delivery of anti-inflammatory therapeutics using pH-responsive histidine-modified poly-L-lysine on mesoporous silica nanoparticles - Permana, Zuliar; Xeliem, Jovinka N.; Zefrina, Normalita F.; Hanum, Latifa F.; Nirmalayanti, Ni LPKV.; Permana, Benny; Mudhakir, Diky (Narra J, 2025)
Mesoporous silica nanoparticles (MSNs) are effective platforms for drug delivery due to their high surface area, adjustable pore sizes, and biocompatibility. The aim of this study was to explore the application of histidine-modified poly-L-lysine (PLL-His) as a pH-responsive gatekeeper to control the release of an anti-inflammatory agent, celecoxib, from MSNs. MSNs were synthesized through a sol-gel process using cetyltrimethylammonium bromide (CTAB) as a template and were functionalized with amine groups using (3-aminopropyl)triethoxysilane (APTES). Drug loading was achieved via adsorption in ethanol. Subsequently, poly-L-lysine (PLL) and PLL-His were conjugated to the MSNs using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDAC) and N-hydroxysuccinimide (NHS) to form MSN-NH2-Drug-PLL and MSN-NH2-Drug-PLL-His constructs. Characterization of these particles was conducted using Fourier-transform infrared (FT-IR) spectroscopy, Brunauer-Emmett-Teller (BET) analysis, and particle size analysis. Results showed that the particle size of MSN-NH2-drug-PLL and MSN-NH2-drug-PLL-His was 237.10±6.56 nm and 234.03±14.65 nm, respectively, indicating suitability for cellular uptake. BET analysis confirmed the increased surface area and pore volume after the removal of CTAB, demonstrating successful mesopore formation. Drug release tests were performed in simulated gastric (pH 1.2) and physiological (pH 7.4) conditions, showing that PLL-His-modified MSNs exhibited minimal release in acidic conditions and sustained release at physiological pH. The PLL-His effectively functioned as a pH-responsive gatekeeper, enhancing drug targeting and reducing premature release. This study highlights the potential of PLL-His-modified MSNs as a promising model for pH-sensitive, targeted drug delivery, with potential applications across various therapeutic areas requiring precise release profiles. This approach could significantly improve therapeutic outcomes and patient compliance, particularly in disease contexts where pH variability is a critical factor. Overall, the integration of PLL-His as a pH-responsive gatekeeper represents a significant advancement in the design of smart drug delivery systems.